“I Have to Take A Deep Breath”: Emotional Geography of EFL Lecturers During Undergraduate Thesis Supervision - Sukarsono; Nanik Sri Rahayu; Muhammad Andrean Syahsurya (JEELS (Journal of English Education and Linguistics Studies), 2023)
Myriad of publications concerning students’ experiences during their final project completion process have been well documented. However, little discussed the supervisors’ emotional geography in fulfilling their task as supervisors for final projects. Therefore, the present study attempts to have an in-depth narrative case study that explores the emotional journeys of two EFL teachers supervising undergraduate thesis. Grounded on Hargreaves' (2001) emotional geography framework, this narrative case study employed direct interviews with EFL lecturers over the course of one month provided the source of the study's data. The study's findings showed that the participant experienced sustainable adaptation through negotiated emotional changes in their experiences as undergraduate thesis supervisors which were anchored by that focuses on physical, social, moral, professional, and political aspects. The findings of this study informed that supervisors experienced different degrees of emotional geographies one of which is caused by the length of supervisory process they have undergone. Pedagogical implications and further studies are also presented.